Comprehensive analysis and validation of angiogenesis in vascular dementia from the perspective of diagnosis, prevention, and treatment - Xu, Lijun; Wang, Yujiao; Xie, Daojun (Frontiers in Genetics, 2025)
BackgroundAngiogenesis is a critical pathological process in vascular dementia (VD), yet current therapeutic strategies targeting this mechanism remain limited. Identifying novel molecular pathways involved in angiogenesis holds significant promise for advancing both diagnostic and therapeutic approaches for VD.MethodsWe first applied weighted gene coexpression network analysis (WGCNA) and differentially expressed gene (DEG) analysis, combined with phenotypic gene database mining, to identify angiogenesis-associated genes in VD. We then used the Least Absolute Shrinkage and Selection Operator (LASSO) regression to select key diagnostic genes. The diagnostic efficacy of these genes was evaluated using receiver operating characteristic (ROC) curve analysis, while their association with immune cell infiltration was assessed via xCell immunoinfiltration. Using single-nucleus RNA sequencing (snRNA-seq), we determined the cellular distribution of key genes and applied Gene Set Enrichment Analysis (GSEA) to analyze functional pathways in the differentially expressed cell clusters. Finally, we validated gene expression changes in the hippocampus of bilateral common carotid artery occlusion (BCCAO)-induced VD rats using quantitative polymerase chain reaction (qPCR) and Western blot (WB).ResultsUltimately, we screened five key genes, namely, CCL2, VEGFA, SPP1, ANGPT2, and ANGPTL4, which were all downregulated in the BCCAO model. The results of snRNA-seq showed that key genes were mainly clustered in microglia, endothelial cells, and astrocytes. Microglia, endothelial cells, and astrocytes play a key role in regulating angiogenesis.ConclusionThese five key genes might be used as angiogenesis diagnostic genes for VD and might be novel potential targets for diagnosis, treatment, and prevention.